Pengaruh Adaptasi Dan Komunikasi Pada Pola Belajar Mahasiswa Di Perguruan Tinggi. - Novandri L. Anin; Tetty Setiawaty; Roly Edyan (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
Adaptation and effective communication are essential for students to cope with academic demands and develop effective learning patterns in higher education. This study aimed to analyze the influence of adaptation and communication on the learning patterns of students in the Building Engineering Education Study Program at Nusa Cendana University. The research employed a quantitative approach using a survey method. A total of 172 students were selected through probability sampling using the simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination analysis. The results revealed that both adaptation and communication had a positive and significant influence on students’ learning patterns, both partially and simultaneously. The coefficient of determination (R²) value of 0.679 indicates that 67.9% of the variation in students’ learning patterns is explained by adaptation and communication, while the remaining 32.1% is influenced by other factors outside the scope of this study.